Improving Writing Skills in Second-Year Students of SMA Negeri 12 Bulukumba Using Problem-Based Illustration Strategy: An Experimental Study - HASRI (Lingedu: Journal of Linguistics and Education, 2026)
ABSTRACT This research applied pre-experimental method. This thesis discusses Developing the Writing Ability of the Second Year Students of SMA Negeri 12 Bulukumba through the Use of Problem Based Illustration Strategy (An Experimental Research). The population was the second year students of SMA Negeri 12 Bulukumba. This research used one group pre-test and post-test design. The sample of this research was the second year students of SMA Negeri 12 Bulukumba and used cluster random sampling technique. Instrument of the research was writing test. The writing test consisted of pre-test and post-test is used to see the students writing ability after giving treatment. The result of this research is gotten by comparing the pre-test and post-test score, then analyzed it by using t-test formula and finally shows t-test = 17.63 than this value is measured into t-table with the level of significance (α) 0.05, degree of freedom (df) = 19, and finally it was found the value of t-table shows = 2.093. Based on the result, researcher concludes there is significance development in writing ability of the students after giving treatment.     Keywords: Problem Based Illustration Strategy, Writing Ability, Experimental Research